ESG, INTEGRATED REPORTING, AUDIT AND FIRM VALUE: EVIDENCE FROM ASEAN-5 CARBON-INTENSIVE SECTORS - Hakim, Tito IM. Rahman; Muhammad, Erfan; Rohma, Frida Fanani; Maulana, Ghifari Robby; Putri, Ervina Rahmalia; Osman, Diaeldin (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2026)
Purpose – This study’s objective is to probe the nexus of ESG and IR on firm value moderated by audit committee characteristics and auditor tenure. Methods – The study employed panel data regression across the mining and property sector in ASEAN-5 countries spanning from 2021-2023.   Findings – This study reveals that ESG and IR fail to contribute significantly to firm value creation. Audit committee expertise emerges as the sole significant moderating variable, surprisingly weakening the relationship between ESG, IR, and firm value. Research Implications – Future studies should refine the measurement of audit committee expertise to better fit the sustainability context. Investors in the ASEAN-5 region appear largely indifferent to ESG and IR information, which discourages mining and property companies from seeking adequate assurance for their non-financial reports. Furthermore, policymakers are urged to devise superior regulations to enhance the credibility of ESG and IR disclosures and establish robust governance mechanisms. Originality – This study is the first in combining internal and external audit function to moderate the effect of sustainability initiatives on firm value in ASEAN-5 context.